PROMIS Physical Function Correlates with KOOS, JR in Patients with Knee Pain - Kortlever, Joost T. P.; Leyton-Mange, Andrea; Keulen, Mark H. F.; Liu, Tiffany C.; Janssen, Stein J.; Bozic, Kevin J.; Schultz, W. Randall; Koenig, Karl M. (The Journal of Knee Surgery, 2019)
Using Patient-Reported Outcomes Measurement Information System Physical Function (PROMIS PF) computerized adaptive test instead of the Knee injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS, JR) could reduce question burden for patients with knee pain. We aimed to prospectively determine the correlation between PROMIS PF and KOOS, JR to assess whether PROMIS PF could be a useful alternative measure for both research and clinical care of patients with knee pain. This was a cross-sectional study of 88 patients. We assessed the correlation between PROMIS PF and KOOS, JR using a Pearson's correlation test. Two multivariable linear regression models were used to determine the amount of variation explained by various patient-level factors. There was a strong correlation between PROMIS PF and KOOS, JR (r = 0.74, p < 0.001). KOOS, JR was an independent predictor of PROMIS PF when controlling for patient-level factors (β 0.26; p < 0.001). The results of this study support the idea of using PROMIS PF in place of joint-specific measures such as KOOS, JR for clinical care of patients with knee pain. The level of evidence for this study is Level III.
Keywords: PROMIS PF; KOOS; JR; knee; osteoarthritis; physical function